Assessing Region of Interest Schemes for the Corticospinal Tract in Patients With Brain Tumors. Issue 12 (March 2016) - Niu, Chen; Liu, Xin; Yang, Yong; Zhang, Kun; Min, Zhigang; Wang, Maode; Li, Wenfei; Guo, Liping; Lin, Pan; Zhang, Ming
Abstract : Abstract: Diffusion tensor imaging (DTI) and diffusion tensor tractography (DTT) techniques are widely used for identifying the corticospinal tract (CST) white matter pathways as part of presurgical planning. However, mass effects in patients with brain tumors tend to cause anatomical distortions and compensatory functional reorganization of the cortex, which may lead to inaccurate mapping of white matter tracts. To overcome these problems, we compared different region-of-interest (ROI) selection schemes to track CST fibers in patients with brain tumors. Our study investigated the CSTs of 16 patients with intracranial tumors. The patients were classified into 3 subgroups according to the spatial relationships of the lesion and the primary motor cortex (PMC)/internal capsule. Specifically, we investigated the key factors that cause distorted tractography in patients with tumors. We compared 3 CST tractography methods that used different ROI selection schemes. The results indicate that CST fiber tracking methods based only on anatomical ROIs could possibly lead to distortions near the PMC region and may be unable to effectively localize the PMC. In contrast, the dual ROI method, which uses ROIs that have been selected from both blood oxygen level-dependent functional MRI (BOLD-fMRI) activation and anatomical landmarks, enabled the tracking of fibers to the motor cortex. The results demonstrate that the dual ROI method can localize the entire CST fiber pathway and can accurately describe the spatial relationships of CST fibers relative to the tumor. These results illustrate the reliability of using fMRI-guided DTT in patients with tumors. The combination of fMRI and anatomical information enhances the identification of tracts of interest in brains with anatomical deformations, which provides neurosurgeons with a more accurate approach for visualizing and localizing white matter fiber tracts in patients with brain tumors. This approach enhances surgical performance and perserves brain function. Abstract : Supplemental Digital Content is available in the text